Verba Majemuk Bahasa Banjar Hulu: Tinjauan Bentuk Gramatikal - Asnawi, Asnawi; Mukhlis, Muhammad (GERAM: Gerakan Aktif Menulis, 2018)
This study presents a related problem about the compound verbs in the Banjar Hulu language. Banjar language is the language used by the people of Indragiri Hilir Regency Riau. At present the state of the Banjar Hulu language is contaminated with modern culture and technology. Therefore, an in-depth study of the language of Banjar Hulu is needed. The problem that is examined is related to the form of the compound verb Banjar Hulu. The purpose of this study was to describe and explain in detail about the compound verbs in the Banjar Hulu language. This research is a type of field research using descriptive method. The research data is in the form of words spoken by the informant, with competent involvement data collection techniques. Data validation is done by triangulating the source by analyzing data regarding the original form and basic form. The results of this study are the discovery of the first basic compound verbs (a) basic compound verbs with the second noun component, (b) compound verbs with the first component adjectives, (c) basic compound verbs with the second component adjectives, (d) basic compound verbs with the first component adverb, (e) basic compound verb with both verb components. The two affiliated compound verbs; (a) affiliated compound verbs with the base of the components, (b) affixed compound verbs with the base of the free form, (c) affixed compound verbs with the two beraphyx components. The three compound verbs repeated.